Submarine Groundwater Discharge From Sediments and Sand Boils Quantified by the Mean Residence Time of a Tracer Injection - Schlüter, Michael; Maier, Philipp (Frontiers in Earth Science, 2021)
For quantification of Submarine Groundwater Discharge, we developed an inexpensive automated seepage meter, which applies a tracer injection and the computation of the Mean Residence Time. The SGD-MRT is designed to measure a wide range of discharge rates from about 60 to 800 cm³ min-1 and allows minimizing backpressures caused by pipe friction or flow sensors. By modifying the inner volume of the flow-through unit, the range of measurement is adjustable. For process control and data acquisition, an Arduino controller board is used. In addition, components like temperature and pressure sensors or pumps add to the SGD-MRT. During field tests in the Wadden Sea, covering tidal cycles, discharge rates of more than 700 cm³ min-1 released from sand boils. Based on the measured discharge rates and numerical integration of the time-series data, a water volume of about 400 dm3 with a seawater content of less than 12% release from the sand boil within seven hours.